2010
DOI: 10.1039/b925968f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacterial cells by impedance spectra via fluidic electrodes in a microfluidic device

Abstract: In this study, a novel method for detecting bacterial cells in deionized (DI) water suspension is presented by using fluidic electrodes with a hydrodynamic focusing technique. KCl solution was utilized as both sheath flow and fluidic electrodes, and the bacterial suspension was squeezed to form three flowing layers with different conductivities on a microfluidic chip. An impedance analyzer was connected with the KCl solution through two Ag/AgCl wires to apply an AC voltage to fluidic layers within a certain fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The detection limit was also shown comparable with many label-free immunosensors for detection of pathogenic bacteria [5]. Zhu and co-workers [18] recently reported a linear relationship between the impedance and the logarithmic value of the bacterial concentration in certain cell concentration ranges for Porphyromonas gingivalis and Escherichia coli. Different from these studies, another study has demonstrated that use of bacterial impedance together with a dielectrophoretic manipulation can differentiate between different Bacillus species through monitoring current change caused by different species [19].…”
supporting
confidence: 64%
“…The detection limit was also shown comparable with many label-free immunosensors for detection of pathogenic bacteria [5]. Zhu and co-workers [18] recently reported a linear relationship between the impedance and the logarithmic value of the bacterial concentration in certain cell concentration ranges for Porphyromonas gingivalis and Escherichia coli. Different from these studies, another study has demonstrated that use of bacterial impedance together with a dielectrophoretic manipulation can differentiate between different Bacillus species through monitoring current change caused by different species [19].…”
supporting
confidence: 64%
“…Gottschamel et al [88] developed a disposable microfluidics biochip for multiparameter Candida albicans population measurements, which can monitor Candida albicans growth rates and metabolic activities by simultaneous bioimpedance spectroscopy and amperometric measurements. Zhu et al [92] used fluidic electrodes to fabricate a microfluidics device for detecting bacterial cells in deionized water suspensions with a detection limit of 10 3 cfu·mL −1 . KCl solution was utilized as both sheath flow and fluidic electrodes, and the bacterial suspension was squeezed to form three flowing layers with different conductivities on a microfluidics chip.…”
Section: Microfluidics Techniquesmentioning
confidence: 99%
“…Coupled with the physics-based models, in practice, one needs analytical techniques to assess the electrical response of the sample. Particularly, for biological cells, the electrical impedance spectroscopy (EIS) [6] is widely accepted as a label-free, non-invasive and quantitative analytical method that can thoroughly assess the electrical properties of biological cells [7].…”
Section: Introductionmentioning
confidence: 99%